The elasticity of trade: Estimates and evidence - Ina Simonovska; Michael E. Waugh (Center for Economic Studies and ifo Institute (CESifo), 2011)
Quantitative results from a large class of international trade models depend critically on the elasticity of trade with respect to trade frictions. We develop a simulated method of moments estimator to estimate this elasticity from disaggregate price and trade-flow data using the Ricardian model. We motivate our estimator by proving that the estimator developed in Eaton and Kortum (2002) is biased in any finite sample. We quantitatively show that the bias is severe and that the data requirements necessary to eliminate it in practice are extreme. Applying our estimator to new disaggregate price and trade-flow data for 123 countries in the year 2004 yields a trade elasticity of roughly four, nearly fifty percent lower than Eaton and Kortum's (2002) approach. This difference doubles the welfare gains from international trade.
Keywords: F10; F11; F14; F17; 330; elasticity of trade; bilateral; gravity; price dispersion; indirect inference; Außenwirtschaft; Außenhandelsbeschränkung; Elastizität; Außenhandelsliberalisierung; Wohlfahrtseffekt; Welt